Investigating Speech Acts in “Miss Perfect”: A Pragmatic Perspective - Maria Permata Florensia (PRAGMATICA : Journal of Linguistics and Literature, 2025)
This study examines the use of speech acts in the short film “Miss Perfect” directed by Jinnyboy TV from a pragmatic perspective. Utilizing the theoretical frameworks of Austin (1962) and Searle (1969), the research explores how language functions as action within cinematic dialogue. A qualitative descriptive method was employed to analyze the film's script, focusing on identifying locutionary, illocutionary, and perlocutionary acts. Particular attention was given to Searle’s (1976) classification of illocutionary acts: assertives, directives, commissives, expressives, and declaratives. The findings reveal that all three types of speech acts are evident in the film, with illocutionary acts being the most dominant. Characters use language not only to convey information but also to express emotions, make requests, give commands, make promises, and influence others. These speech acts contribute significantly to the development of character relationships and the narrative structure. For instance, assertives are used to state opinions and beliefs, directives to give instructions or commands, commissives to express commitments, expressives to convey emotions, and declaratives to enact social functions. This analysis highlights how speech acts in film dialogue mirror real-life communication and provide insight into the social and emotional dynamics of the characters. The study underscores the value of applying pragmatic theory to media texts, offering a deeper understanding of how language constructs meaning in scripted narratives.